548 CD8+ tissue-resident memory T cells are tumour reactive and increase after immunotherapy in a case of metastatic mucosal melanoma. (9th November 2020) - Pizzolla, Angela; Keam, Simon; Vergara, Ismael; Caramia, Franco; Wang, Minyu; Kocovski, Nikolce; Nguyen, ThuNgoc; Macdonald, Sean; Tantalo, Daniela; Petrone, Pasquale; Aw Yeang, Han Xian; Gyorki, David; et al.
Abstract : Background: Mucosal melanoma is a rare subtype of melanoma originating from mucosal tissues, 1 metastases are very aggressive and respond poorly to therapy, including immune checkpoint inhibitors (ICI) such as anti-CTLA4 and anti-PD1 antibodies. 2–5 CD8+ T cells constitute the most abundant immune infiltrate in metastatic melanoma, of which the Tissue Resident Memory subset (TRM) is of particular interest. 6 CD8+ TRM cells express the highest levels of immune checkpoint receptors, proliferate in response to ICI and correlate with longer disease-free and overall survival. 6–8 The immune landscape in mucosal melanoma remains poorly characterized. We aimed to: 1) phenotype CD8+ T cells and TRM infiltrating metastatic mucosal melanoma, 2) characterize the clonality of TRM in relation to other CD8+ T cell subsets and 3) define the capacity of CD8+ T cells and TRM to respond to melanoma cells and to in vivo and in vitro anti-PD1 treatment. Methods: We investigated the CD8+ T and TRM cells infiltrating two temporally- and spatially-distant subcutaneous metastases, these originated from a primary vaginal mucosal melanoma. One metastasis was excised prior to anti-PD1 treatment and one was anti-PD1 refractory, having progressed on treatment. We used mass cytometry and single-cell RNA and TCR sequencing to characterise the phenotype and clonality of the T cells, multiplex immunohistochemistry to define their spatial relationship with tumour cells and other T cells, and functional assays to determine TRM response to tumour cells (figure 1 ). Results: CD8+ TRM frequency increased with time and anti-PD1 treatment, forming clusters at the tumour margin. T cells in the anti-PD1 refractory lesion were more activated than T cells in the first tumour and were bound by anti-PD1 antibody in vivo. T cells could not be stimulated by anti-PD1 directly ex vivo. Both metastatic lesions shared common T cell clusters including TRM. Furthermore, TRM in each tumour shared T cell clones, suggesting the presence of common antigens between metastatic sites. Indeed, the two metastases had a similar mutational profile. In vitro expanded tumour infiltrating lymphocytes from both lesions recognized tumour cells from both lesions and the same neoantigen generated from a single point mutation in the gene CDKN1C. Finally, tumour cells stimulated TRM cells more robustly than other T cells subsets. Conclusions: In this patient with vaginal mucosal melanoma, subsequent melanoma metastases of clonal origin attracted CD8+ T cells of similar specificity, among which TRM cells responded more vigorously to tumour cells than other T cells subsets. Acknowledgements: The authors would like to acknowledge imCORE La Hoffmann- Roche Ltd. for funding. Ethics Approval: Patients diagnosed with stage 3 or 4 metastatic melanoma and undergoing clinically indicated surgery were enrolled in prospective studies approved by the Peter MacCallum Cancer Centre human ethics research committee (13/141). All experimental protocols have been approved and clinical data has been collected prospectively. References: Carvajal RD, Hamid O, Ariyan C. Mucosal Melanoma. [cited 2020 Apr 1]; Available from: https://www.uptodate.com/contents/mucosal-melanoma Del Vecchio M, Di Guardo L, Ascierto PA, Grimaldi AM, Sileni VC, Pigozzo J, et al. Efficacy and safety of ipilimumab 3 mg/kg in patients with pretreated, metastatic, mucosal melanoma. Eur J Cancer Oxf Engl 1990; 2014 Jan;50(1):121–7. Postow MA, Luke JJ, Bluth MJ, Ramaiya N, Panageas KS, Lawrence DP, et al. Ipilimumab for patients with advanced mucosal melanoma. The Oncologist 2013 Jun;18(6):726–32. D'Angelo SP, Larkin J, Sosman JA, Lebbé C, Brady B, Neyns B, et al. Efficacy and safety of nivolumab alone or in combination with ipilimumab in patients with mucosal melanoma: a pooled analysis. J Clin Oncol Off J Am Soc Clin Oncol . 2017 Jan 10;35(2):226–35. Hamid O, Robert C, Ribas A, Hodi FS, Walpole E, Daud A, et al. Antitumour activity of pembrolizumab in advanced mucosal melanoma: a post-hoc analysis of KEYNOTE-001, 002, 006. Br J Cancer 2018;119(6):670–4. Boddupalli CS, Bar N, Kadaveru K, Krauthammer M, Pornputtapong N, Mai Z, et al . Interlesional diversity of T cell receptors in melanoma with immune checkpoints enriched in tissue-resident memory T cells. JCI Insight [Internet]. 2016 Dec 22 [cited 2019 Apr 24];1(21). Available from: https://insight.jci.org/articles/view/88955 Edwards J, Wilmott JS, Madore J, Gide TN, Quek C, Tasker A, et al. CD103+ Tumor-resident CD8+ T cells are associated with improved survival in immunotherapy-naïve melanoma patients and expand significantly during anti-PD-1 treatment. Clin Cancer Res Off J Am Assoc Cancer Res 2018 Jul 1;24(13):3036–45. Savas P, Virassamy B, Ye C, Salim A, Mintoff CP, Caramia F, et al. Single-cell profiling of breast cancer T cells reveals a tissue-resident memory subset associated with improved prognosis. Nat Med 2018 Jul;24(7):986–93.